A case series on resin allergy during clear aligner therapy - Mohamed Alizae Marny Fadzlin Syed; Nee Tey Sock; Hongli Milton Tsai; Ashari Asma; Kasim Noor Hayaty Abu (Australasian Orthodontic Journal, 2025)
Clear aligner therapy (CAT) has gained popularity due to its aesthetic benefits, especially among adults. However, with ongoing advancements in appliance materials, concerns about resin allergies have emerged because of the extended contact between aligner plastics and the oral tissues. This case series highlights important clinical features of this rare and increasingly recognised issue. Diagnosing the allergies proved challenging due to variability in the presentation and test results. All of the cases were females aged 23 to 28 years with no prior history of allergy to food nor dental materials. Clinical manifestations varied between the patients and ranged from redness and swelling of the lips and gums to numbness and ulceration. Allergy testing, including serum immunoglobulin E (IgE) and patch tests, yielded inconsistent results for two of the cases. Therefore, diagnosis was based primarily on clinical signs and symptoms. CAT was discontinued for two of the patients. In conclusion, it is crucial for dental practitioners to be aware of hypersensitivity reactions and thereby facilitate early detection of resin allergies in patients undergoing CAT.